2016
DOI: 10.12693/aphyspola.129.785
|View full text |Cite
|
Sign up to set email alerts
|

Technology and Investigation of Ohmic Contacts to Thermoelectric Materials

Abstract: Technology is developed, materials and regimes of the fabrication of ohmic contacts to the effective thermoelectric materials Bi2Te2.8Se0.2 (n-type) and Bi0.5Sb1.5Te3 (p-type) are determined. Ohmic contacts were obtained by the vacuum deposition of nickel. Factors determining adhesion strength and resistivity of fabricated contacts are determined. Process of surface preparation of the thermoelectric materials before the ohmic contact deposition is optimized during the technology development. The use of electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…However, metallization using barrier layers at both the ends of the thermoelectric legs can enrich the wettability of the solder and can restrict the diffusion of the solder into the thermoelectric material. An ohmic contact is essential to minimize the parasitic losses evolving due to the additional thermal and electrical resistance at the boundary [70–71] . If Rc ${{R}_{c}}$ is the electrical contact resistances at the interface of the contact and thermoelectric material, then it can be obtained by subtracting the resistance of the material and the resistances due to wiring from the total resistance of the module.…”
Section: Working Principle and Engineering Standpoint Of Thermoelectr...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, metallization using barrier layers at both the ends of the thermoelectric legs can enrich the wettability of the solder and can restrict the diffusion of the solder into the thermoelectric material. An ohmic contact is essential to minimize the parasitic losses evolving due to the additional thermal and electrical resistance at the boundary [70–71] . If Rc ${{R}_{c}}$ is the electrical contact resistances at the interface of the contact and thermoelectric material, then it can be obtained by subtracting the resistance of the material and the resistances due to wiring from the total resistance of the module.…”
Section: Working Principle and Engineering Standpoint Of Thermoelectr...mentioning
confidence: 99%
“…An ohmic contact is essential to minimize the parasitic losses evolving due to the additional thermal and electrical resistance at the boundary. [70][71] If R c is the electrical contact resistances at the interface of the contact and thermoelectric material, then it can be obtained by subtracting the resistance of the material and the resistances due to wiring from the total resistance of the module. R c also considers the effect of the area in contact.…”
Section: Working Principle and Engineering Standpoint Of Thermoelectr...mentioning
confidence: 99%
“…Different metallization techniques have been investigated for other thermoelectric materials. For instance, electroplating followed by thermo-compression bonding has been reported for indium contacts with nickel diffusion barriers on Bi 2 Te 3 , 10 while Shtern et al 11 reported on the optimization of evaporated Ni films for contacts to Bi 0.5 Sb 1.5 Te 3 and Bi 2 Te 2.8 Se 0.2 , and Jung et al 12 presented a review on the lead free transient liquid phase soldering addressing thermoelectrics. Yet, there are only a few reports on the metallization of ZnSb.…”
Section: Introductionmentioning
confidence: 99%